The impact of COVID-19 on safe abortion access in Africa: An analysis through a framework of reproductive justice and lens of structural violence - Tiew, Amanda; Berro Pizzarossa, Lucía; Jastaniah, Ibtehal; Jayaweera, Ruvani T. (Frontiers in Global Women's Health, 2022)
The SARS-CoV-2 virus causing the coronavirus disease (COVID-19) global pandemic heightened restrictions on sexual and reproductive health and rights (SRHR), especially concerning safe abortion access. The African region has been particularly susceptible to the impact of COVID-19 on sexual and reproductive health services, coupled with a high prevalence, having the highest rates of unsafe abortion and maternal mortality in the world. A reproductive justice framework posits safe abortion access amongst social power relations. Adding to that, the framework of structural violence aims to make structural health inequalities visible outside of the individual lived experience. Using these frameworks, we interviewed key informants from the Mobilizing Action around Medication Abortion (MAMA) Network regarding the impacts of structural violence and COVID-19 on SRHR programming in Africa, particularly programming on self-managed abortion. We identified themes of lacking infrastructures of support, emergent marginality, and neocolonial funding environments as facets of structural violence within the context of the MAMA Network, as heightened by the COVID-19 global pandemic.